Conservative Treatment of Hangman Variant Fractures. Issue 5 (June 2018) - Niemeier, Thomas E.; Manoharan, Sakthevil R.; Mukherjee, Amrita; Theiss, Steven M.
Abstract : Study Design: This is retrospective cohort study. Objective: Investigate the stability of patients with hangman variant fractures and outcomes of treatment with external immobilization. Summary of Background Data: Traumatic spondylolisthesis of the axis (C2) with the fracture extending into the vertebral body has been incompletely characterized. Small case series have showed high rates of neurological injury and cite difficulty treating closed due to greater instability secondary to extensive ligamentous injury. Materials and Methods: Retrospectively, all patients admitted to a level 1 trauma center from 2004 to 2015 with acute C2 fractures were identified and classified based on computed tomographic imaging. Study cohort included patients with anterior translation <5 mm and C2–3 angulation <15 degrees that were followed to conclusion of treatment. Results: In total, 107 hangman's variant fractures (14.5%) were identified from a database of 735 acute C2 fractures. In total, 106 of the 107 patients displayed no neurological injury related to the cervical spine at the time of presentation. A total of 63 patients met the inclusion criteria and were followed as outpatients until collar or halo vest removal. All fractures progressed to union without progressive displacement or late neurological injury. No difference was observed in radiographic outcome between patients treated in a hard collar versus halo orthosis. Conclusions: Although widely considered a difficult fracture to treat with closed means, hangman variants are relatively neurologically benign injuries with low incidence of ligamentous injury. Fractures with <5 mm of horizontal translation and 15 degrees of angulation can be treated with external immobilization. Our results suggest no advantage of halo immobilization versus hard collar orthosis.